PENDAMPINGAN MELAWAN ISLAMOFOBIA DAN UJARAN KEBENCIAN DI MEDIA SOSIAL BAGI KARANG TARUNA SETIABUDI JAKARTA SELATAN - Pamungkas, Andhika; Said Matondang, Ahmad (LPPM Univ. Ibn Khaldun Bogor, 2022)
Islamophobia is an act that leads to violence and hatred against Muslims. Initially, Islamophobia occurred in the real world where several Muslims who were a minority received harsh and intimidating treatment from the majority population. Apart from real life, Islamophobia has also penetrated the internet and social media. On the internet, everyone can produce information content according to their own will. This is why Islamophobia and hate speech can be found on the internet and social media. If in the mass media Islamophobic content and hate speech can still be filtered out with parental supervision, it is different from the internet and social media. These contents can easily reach teenagers' devices. To prevent these contents from damaging the minds of teenagers, education is needed to equip them against Islamophobia and hate speech. This service program in the form of mentoring has a target to provide understanding to members of Karang Taruna Setiabudi, South Jakarta, about the dangers of Islamophobic content and hate speech. So that partners can know the characteristics of the negative content, and not disseminate it or be able to fight the narrative in the content in a way that does not violate the law.